From Finding a Niche to Circumventing Institutional Constraints: Examining the Links Between Academics’ Online Networking, Institutional Roles, and Identity-Trajectory - Jordan, Katy (International Review of Research in Open and Distributed Learning, 2019)
Academics are increasingly encouraged to use social media in their professional lives. Social networking sites are one type of tool within this; the ability to connect with others through this medium may offer benefits in terms of reaching novel audiences, enhancing research impact, discovering collaborators, and drawing on a wider network of expertise and knowledge. However, little research has focused on the role of these sites in practice, and their relationship to academics’ formal roles and institutions. This paper presents an analysis of 18 interviews carried out with academics in order to discuss their online networks (at either Academia.edu or ResearchGate, and Twitter) and to understand the relationship between their online networks and formal academic identity. Several strategies underpinning academics’ use of the sites were identified, including: circumventing institutional constraints, extending academic space, finding a niche, promotion and impact, and academic freedom. These themes also provide a bridge between academic identity development online and institutional roles, with different priorities for engaging with online networks being associated with different career stages.